Maurice Blanchot and the image of death (Nóema, 2013)
Journalist, literary critic, novelist and essayist, Maurice Blanchot has always questioned the uncertain limit between philosophical and fictional languages. The purpose of this article is to underline his constant inquiry of the connection between his own writing activity and political participation, through which he managed to describe, theorize and realize a true dissolution of subject.
Keywords: Maurice Blanchot; Terror; Death; Image; Politics; Literature; Subject